2017
DOI: 10.1111/febs.14018
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of α‐galactosyl oligosaccharides using a mutant Bacteroides thetaiotaomicron retaining α‐galactosidase (BtGH97b)

Abstract: Abbreviations: α-GalF, α-galactopyranosyl fluoride; Gal-Lac, β-lactosyl α-D-galactopyranoside; 20 GH, glycoside hydrolase family; HMBC, heteronuclear multiple bond correlation; 21 high-performance anion exchange chromatography-pulsed amperometric detection. The preparation of a glycosynthase, a catalytic nucleophile mutant of a glycosidase, is a well-5 established strategy for the effective synthesis of glycosidic linkages. However, glycosynthases 6 derived from α-glycosidases can give poor yields of desired p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
(298 reference statements)
1
13
1
Order By: Relevance
“…Surprisingly, all the catalytic nucleophile mutants exhibited a non-negligible residual hydrolytic activity with pNP-β-Gal substrate. This is in contrast to previous findings on other glycosynthases in the literature [12,17] -it has been generally accepted so far that this type of mutation leads to the complete abolishment of hydrolytic activity in retaining glycosidases. We also considered the issue of translational misincorporation [34] that might have resulted in the contamination of mutant enzyme samples by traces of WT enzyme.…”
Section: Chemcatchemcontrasting
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, all the catalytic nucleophile mutants exhibited a non-negligible residual hydrolytic activity with pNP-β-Gal substrate. This is in contrast to previous findings on other glycosynthases in the literature [12,17] -it has been generally accepted so far that this type of mutation leads to the complete abolishment of hydrolytic activity in retaining glycosidases. We also considered the issue of translational misincorporation [34] that might have resulted in the contamination of mutant enzyme samples by traces of WT enzyme.…”
Section: Chemcatchemcontrasting
confidence: 99%
“…When the nucleophile (Asp or Glu) is replaced by a non-nucleophilic residue, it affords a glycosynthase -a hydrolytically inactive enzyme unable to form the glycosyl-enzyme intermediate. [12,16,17] It is possible to rescue the activity of glycosynthases using an activated substrate of the 'correct' anomeric configuration by adding smallmolecule exogenous nucleophiles (sodium azide or sodium…”
Section: Introductionmentioning
confidence: 99%
“…The only previously reported engineering of BbAfcB is its transformation into an α-L-fucosynthase, giving an LNFP II yield of 41% when using 34 times more enzyme than in the current work [22]. While this strategy is appealing due to its simple, generic nature, especially αglycosynthases struggle with low donor substrate stability [22,44]. GH29B α-1,3/4-L-fucosidases are particularly appealing in terms of engineering for improved transfucosylation activityand for use in transfucosylation in generalsince they appear to maintain their high regioselectivity in the transfucosylation reaction, while the GH29A α-Lfucosidases often do not [10,12,22].…”
Section: Discussionmentioning
confidence: 79%
“…Cobucci-Ponzano et al reported the effective conversion of β- d -galactopyranosyl azide ( 35 , βGalN 3 ) to α-galacto-oligosaccharides by the glycosynthase TmGalA D327G derived from T. maritima [ 40 ]. The enzyme produced galacto-oligosaccharides in good yields and the method was recently expanded by Okuyama et al to the in situ formation of a β- d -galactosyl formate donor ( 36 ), which exhibited a higher transglycosylation rate compared to the azide donor ( 35 , Scheme 6 ) [ 41 ]. The method allowed the galactosylation of carbohydrates such as glucose (α-1,1-β), xylose (α-1,4), maltose (α-1,1-β), cellobiose (α-1,1-β; α-1,6), lactose (α-1,1-β), and pNP derivatives of glucose (pNPGlc, 37 ), and mannose (pNPMan, 6 ; exclusively α-1,6) in yields ranging from 75 to 95%.…”
Section: Glycoside Syntheses Using Glycosynthase Methodsmentioning
confidence: 99%
“… In situ formation of the glycosyl donors βGalN 3 ( 35 ) or βGal formate ( 36 ) by incubation of αGalF ( 2 ) with glycosynthase BtGH97b D415G the additional external nucleophiles sodium azide of formate [ 41 ]. The in situ produced donor can then be subsequently transferred to a suitable acceptor (R 2 OH).…”
Section: Schemes and Tablesmentioning
confidence: 99%